INTEGRATING ISLAMIC VALUES INTO THE DEVELOPMENT OF ANNOUNCEMENT AND NOTICE UNIT FOR THE EIGHTH GRADE IN MTs MADANI PAO-PAO - Andi Zahra; Andi Asmawati; Kamsinah Kamsinah (Universitas islam Negeri Alauddin Makassar, 2021)
English material that is used in the school is too general. It is also already not reflecting Islam itself. To maintain students’ identity as Muslim, this paper is aimed to integrate Islamic Values into English material especially in basic competences 3.12 and 4.12 about Announcement and Notice for the eighth-grade students at MTs Madani Pao-Pao based on 2013 curriculum. The research design used in this study was Research and Development (R & D). The development model used was ADDIE model. It consists of need analysis, design, development, implementation, and evaluation. The procedures included analyzing materials needed by spreading questionnaire to the students and analyzing the basic competences used, designing a blueprint of materials, and developing the English materials through ADDIE model. In this research, the expert was involved in order to validate the product. There were two systematic aspects the product that they validated: the aspect of the content/material and aspect of learning. Therefore, the result indicated that based on experts’ judgment as well as product development result, the developed basic competences 3.12 and 4.12 was applicable to be taught at the eighth-grade students of Junior High School as topics in English.